Who's up to the challenge? 61

Calculus Level 5

n = 1 Γ ( n + 1 2 ) n 2 Γ ( n ) = A π B ln C \sum _{ n=1 }^{ \infty }{ \frac { \Gamma \left( n+\frac { 1 }{ 2 } \right) }{ { n }^{ 2 }\Gamma (n) } } =A\sqrt [ B ]{ \pi } \ln { C }

If the above equation holds true for positive integers A A , B B and C C , where C C is square-free, then find A B C ABC .

Notation : Γ ( ) \Gamma(\cdot) denotes the Gamma function .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

First Last
Jul 6, 2017

n = 1 Γ ( n + 1 2 ) n 2 Γ ( n ) = π n = 1 ( 2 n 1 ) ! ! n ( 2 n ) ! ! \displaystyle\sum_{n=1}^\infty\frac{\Gamma(n+\frac1{2})}{n^2\Gamma(n)}=\sqrt{\pi}\sum_{n=1}^\infty\frac{(2n-1)!!}{n(2n)!!}

Using the taylor series for arcsin ( x ) = 1 + 1 2 x 3 3 + 1 × 3 2 × 4 x 5 5 + . . . \displaystyle\arcsin(x) = 1+\frac1{2}\frac{x^3}{3}+\frac{1\times3}{2\times4}\frac{x^5}{5}+...

1 1 x = n = 1 ( 2 n 1 ) ! ! ( 2 n ) ! ! x n + 1 \displaystyle\frac1{\sqrt{1-x}}=\sum_{n=1}^\infty\frac{(2n-1)!!}{(2n)!!}x^n+1

1 x 1 x 1 x = n = 1 ( 2 n 1 ) ! ! ( 2 n ) ! ! x n 1 \displaystyle\frac1{x\sqrt{1-x}}-\frac1{x}=\sum_{n=1}^\infty\frac{(2n-1)!!}{(2n)!!}x^{n-1}

π n = 1 ( 2 n 1 ) ! ! n ( 2 n ) ! ! 1 n = π 0 1 n = 1 ( 2 n 1 ) ! ! ( 2 n ) ! ! x n 1 d x = π 0 1 1 x 1 x 1 x d x = 2 π ln 2 \displaystyle\sqrt{\pi}\sum_{n=1}^\infty\frac{(2n-1)!!}{n(2n)!!}1^n=\sqrt{\pi}\int_0^1\sum_{n=1}^\infty\frac{(2n-1)!!}{(2n)!!}x^{n-1}dx=\sqrt{\pi}\int_0^1\frac1{x\sqrt{1-x}}-\frac1{x}dx=2\sqrt{\pi}\ln{2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...